Borders in Service : Enactments of Nationhood in Transnational Call Centres - Poster, Winifred; Mirchandani, Kiran, 1968- (Book collections on Project MUSE., 2016)
In this collection, Kiran Mirchandani and Winifred Poster have gathered a wide range of contributors to explore the dynamics within global call centres.